The opera lover's companion - Osborne, Charles (Yale University Press, 2004)
This engaging guide to the 175 most popular operas will enhance the experience of every opera lover. Written by a well-known authority, the book consists of entries that set each opera within the context of its composer's career, outline the plot, discuss the music, and give relevant background information on the libretto, the staging, and the most famous and influential interpreters of the principal roles. In addition, the entries recount details of the first performance and subsequent performance history and provide guidance on the relative quality of available recordings.Aimed at opera lovers and committed newcomers rather than specialists, The Opera-Lover's Companion does not set out to cover every opera but only those most frequently encountered in opera houses or on recordings. Although the book is dominated by the five great opera composers-Mozart, Verdi, Wagner, Puccini, and Strauss-fifty-eight other composers are also represented. It is always more pleasurable to go to the opera with a knowledgeable and experienced companion. If you can't, you'll want to take this book.
Keywords: Operas : Stories, plots, etc